Technologies to better bounce back from natural disasters.
So far, decision-makers tasked with making their region better prepared for natural disasters have been focusing on improving infrastructures to increase their resistance. But in the face of lukewarm results, the IRUSAT project is proposing to focus on the speed of post-disaster recovery. They developed a virtual city model and a wristband device to enable better emergency response.